SOROCONVERSÃO APÓS VACINA CONTRA HEPATITE B EM PESSOAS VIVENDO COM HIV - NETO, João Borges de Oliveira,; CURY, Eunice Stella Jardim,; MENIN, Iris Bucker Froes,; UEHARA, Silvia Naomi de Oliveira, (ANAIS DO ENIC, 2023)
-